2020
DOI: 10.1371/journal.pone.0232453
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing changes in soil microbiome abundance and diversity due to different cover crop techniques

Abstract: Soil-based microorganisms assume a direct and crucial role in the promotion of soil health, quality and fertility, all factors known to contribute heavily to the quality and yield of agricultural products. Cover cropping, used in both traditional and organic farming, is a particularly efficient and environmentally favorable tool for manipulating microbiome composition in agricultural soils and has had clear benefits for soil quality and crop output. Several longterm investigations have evaluated the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Some experts strongly believe that the abundance of microorganisms in the soil is very important in improving soil and ecosystem quality. Wang et al (2020), who conducted a short-term evaluation of microbial composition and diversity of cover crops, showed that multi-mix better than a single mix. Likewise, Castellano-Hinojosa and Strauss (2020) reviewed that interactions between soil microorganisms, nutrient cycles, and plants will enable the management of a more effective and sustainable annual cropping system.…”
Section: Abundance and Activity Of Soil Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experts strongly believe that the abundance of microorganisms in the soil is very important in improving soil and ecosystem quality. Wang et al (2020), who conducted a short-term evaluation of microbial composition and diversity of cover crops, showed that multi-mix better than a single mix. Likewise, Castellano-Hinojosa and Strauss (2020) reviewed that interactions between soil microorganisms, nutrient cycles, and plants will enable the management of a more effective and sustainable annual cropping system.…”
Section: Abundance and Activity Of Soil Microorganismsmentioning
confidence: 99%
“…The organic C content varies from 1.01% to 1.33% (including low status). Soil microorganisms (particularly those that are beneficial) are rarely evaluated (Miransari, 2016;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plant debris in minimum‐tillage and no‐tillage systems may enhance slow‐release of infochemicals. Plant debris can affect the next crop by modifying the soil microbiome community and activity, by increasing soil fertility, or by acting as an infochemical source (Veen et al, 2019; Wang, Wu, et al, 2020).…”
Section: Wireless Communication: Signal Input‐transfer‐output Modelmentioning
confidence: 99%
“…Plant debris in minimum-tillage and no-tillage systems may enhance slow-release of infochemicals. Plant debris can affect the next crop by modifying the soil microbiome community and activity, by increasing soil fertility, or by acting as an infochemical source (Veen, Fry, ten Hooven, Kardol, Morriën & De Long, 2019, Wang, Wu, Wang, Alabady, Parson, Molumo & Fankhauser, 2020.…”
Section: ? Field Applicationsmentioning
confidence: 99%